Faktor-Faktor yang Mempengaruhi Kualitas Laba - Sebuah Studi Literatur - Carmel Meiden; Rommel Togatorop (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research examines the influence of of audit quality, good corporate governance (GCG), company size, profitability, leverage, financial distress, the effectiveness of the board of commissioners and audit committee, debt policy, ownership structure, and corporate social responsibility (CSR) on earnings quality. It focuses on elements that can affect earnings quality. This literature review summarizes the findings of previous research, exploring the relationships between these factors and earnings quality. This study was conducted by reviewing 13 previous studies related to earnings management and concluding the findings of these studies. Articles reviewed are from within and outside Indonesia with publication time span of 2022-2023. The results are expected to provide insights into the impact on transparency and honesty in financial reporting, with potential implications for regulatory policies and business practices. This study highlights the importance of mitigating earnings quality.